Die mediale Umwelt der Migration: Kulturelle Aushandlungen im 20. und 21. Jahrhundert - Böhm, Roswitha; Tiller, Elisabeth (transcript, 2022)
A critical examination of the cultural network of migration and its medial negotiation – using examples from literature, film and action art, among others.